“Doing extra work and not getting extra help”: the burden of work generated to manage the “no visitors” policy during the COVID-19 pandemic in Ontario, Canada - Jacobson, Danielle; Birze, Arija; Mansfield, Elizabeth; Wodchis, Walter P.; Tang, Terence; Ammi, Mehdi; Guilcher, Sara J. T.; Kuluski, Kerry (Frontiers in Public Health, 2025)
BackgroundDuring the pandemic, a “no visitors” policy was implemented across hospitals in Ontario, Canada. Without caregivers present in-hospital to support patient care (e.g., treatment decision-making, advocacy, treatment compliance, social support), there was a perceived decline in care quality. Despite existing research on the extra work required to navigate the loss of caregiver support in-hospital, there is a paucity of understanding about the work required to manage the “no visitors” policy itself—including creative ways to work around it. This qualitative research study draws attention to the “no visitors” policy and the work to manage and work around these limitations across healthcare system silos (drawing on cancer care and alternate level of care as case examples) in Ontario, Canada.MethodsIn total, 5 focus groups and 53 interviews were conducted with 68 participants (10 patients, 7 caregivers, 40 healthcare providers, and 11 healthcare decision-makers). The authors engaged in codebook thematic analysis.FindingsManaging the “no visitors” policy and pushback against it generated a significant burden of work for patients, caregivers, healthcare providers, and healthcare decision-makers at a time when difficult emotions were high and resources and capacity were low. Five themes are discussed that depict the burden of work: (1) work of making individual exceptions to the “no visitors” policy, (2) work of standardizing exceptions, (3) work to remedy and navigate inconsistencies across hospital units or partner organizations, (4) workarounds to gain in-hospital entry via “hot words” and sneaking in, and (5) workarounds when in-hospital entry was not possible via technology and visiting through windows.ConclusionThe denial of caregivers’ entry into hospitals during the COVID-19 pandemic undermined their value as essential care partners, despite their contributions to patient care. Unintended consequences of such public health policy, including the generation of burdensome work to manage and work around it for all involved, must therefore be more carefully considered for future pandemic preparedness.